Religious ideologies, legitimation, and citizenship in “second republic” Zimbabwe - Nenjerama, Theophilus Tinashe (Critical research on religion, 2025)
In his 2017 rise to the Zimbabwean presidency, Emmerson Mnangagwa conflated religion and politics through, among other strategies, ad nauseum deployment of the phrase: “The voice of the people is the voice of God.” Defining the phrase as dialectical (religious ideology and political philosophy) we explore its intersection with citizenship and legitimation in Zimbabwe’s second republic body politic. By conceptually deploying citizenship and legitimation, we explore contestations on religious discourse and how the two are performed. Our analysis is confined to critical events in the second republic, primarily the 2018 presidential elections and subsequent citizen and church-led social movements. We also observe the preservation of repressive technologies that continue to undercut democratic ideals imbued in Mnangagwa’s religious mantra.